Livestock in a changing landscape. Volume 1. Drivers, consequences, and responses - Steinfeld, H.; Mooney, H.A.; Schneider, F.; Neville, L.E. (Island Press, 2010)
Volume 1 examines the forces shaping change in livestock production and management; the resulting impacts on landscapes, land use, and social systems; and potential policy and management responses.